Shelf-Life Test of Kebab Kebuli Al 'Aqoh for Fulfiling Product Quality of Small Medium Enterprise - Rachmaniah, Orchidea; Rahmawati, Yeni; Kusumahati, Sari; Juliastuti, Sri Rachmania; Hendrianie, Nuniek; Darmawan, Raden; Oktavianingrum, Eva; Fahmi, Fahmi; Meka, Wahyu (Photon: Jurnal Sain dan Kesehatan, 2023)
Al 'Aqoh Drink & Snack, an SME of PKH ITS, participated in a mentoring program in 2021. A series of long-term test storage, microbial contamination tests, and nutritional content tests were conducted for Kebab Kebuli, a product of Al 'Aqoh Drink & Snack, as an implementation of Halal Assurance System (SJH) and Good Manufacturing Practice (GMP). The test results inferred the hygiene of the Kebab Kebuli production process. Freshly made Kebab Kebuli had a total mold value of 2.00 x 101 CFU/g and Escherichia coli of 6.00 x 101 CFU/g. However, other parameters, such as Salmonella sp. and Staphylococcus aureus, were not detected. Although a few mold numbers were detected, ca. 2.00 x 101 CFU/g, an awareness still needs to be applied. Moreover, a non-pathogenic E. coli bacterium, ca. 6.00 x 101 CFU/g, was detected. E. coli can be minimized with good process and post-production sanitation. Therefore, the cooking and reheating process of Kebab Kebuli at 65 oC and subsequent chilling at 4 oC should have been applied. It may have been enough to suppress the growth of E. coli. Hence, it is necessary to process the Kebab Kebuli according to the serving suggestions and to ensure food safety, i.e., avoiding diarrhea.